Lithuanian Language at School: Scientific Insights and Pedagogical Experience - Ona Laima Gudzinevičiūtė; Džiuljeta Maskuliūnienė (Lietuvių Kalba)
The article reviews the issues investigated in the reports and articles developed from the conference reports of the scientific and practical conferences “Mother Tongue at School” organised at Šiauliai University (since 2021, Šiauliai Academy of Vilnius University) in 2012–2022. The aim of the article is to present the journal “Gimtoji kalba mokykloje” [Mother Tongue at School] using the descriptive-analytical method, to discuss topics, problems, aims of the articles, and to summarise the most relevant issues of Lithuanian studies, Lithuanian language and literature teaching (didactics), variations in the Lithuanian language, changes, standardisation, and the importance of Lithuanian literature in developing a thinking and reading individual, conscious of the importance of the native (Lithuanian) language.